Dissection of the genetic architecture for tassel branch number by QTL analysis in two related populations in maize - Zheng-jie CHEN; Cong YANG; Deng-guo TANG; Lei ZHANG; Ling ZHANG; Jing-tao QU; Jian LIU (Journal of Integrative Agriculture, 2017)
Tassel branch number (TBN) is the principal component of maize tassel inflorescence architecture and is a typical quantitative trait controlled by multiple genes. The main objective of this research was to detect quantitative trait loci (QTLs) for TBN. The maize inbred line SICAU1212 was used as the common parent to develop BC1S1 and recombinant inbred line (RIL) populations with inbred lines 3237 and B73, respectively. The two related populations consisted of 123 and 238 lines, respectively. Each population was grown and phenotyped for TBN in two environments. Eleven QTLs were detected in the BC1S1 population, located on chromosomes 2, 3, 5, and 7, accounted for 4.45–26.58% of the phenotypic variation. Two QTLs (qB11Jtbn2-1, qB12Ctbn2-1, qBJtbn2-1; q11JBtbn5-1, qB12Ctbn5-1, qBJtbn5-1) that accounted for more than 10% of the phenotypic variation were identified. Three QTLs located on chromosomes 2, 3 and 5, exhibited stable expression in the two environments. Ten QTLs were detected in the RIL population, located on chromosomes 2, 3, 5, 8, and 10, accounted for 2.69–13.58% of the TBN variation. One QTL (qR14Dtbn2-2) explained >10% of the phenotypic variation. One common QTL (qB12Ctbn2-2, qR14Dtbn2-2, qRJtbn2-2) was detected between the two related populations. Three pairs of epistatic effects were identified between two loci with or without additive effects and accounted for 1.19–4.26% of the phenotypic variance. These results demonstrated that TBN variation was mainly caused by major effects, minor effects and slightly modified by epistatic effects. Thus, identification of QTL for TBN may help elucidate the genetic basis of TBN and also facilitate map-based cloning and marker-assisted selection (MAS) in maize breeding programs.